Reforming Payments and Securities Settlement Systems in Latin America and the Caribbean - Cirasino, Massimo (Washington, DC : World Bank, 2012)
The payments and securities settlement system is the infrastructure (comprising institutions, instruments, rules, procedures, standards, and technical means) established to effect the transfer of monetary value between parties discharging mutual obligations. A securities clearance and settlement system can be considered as part of the overall payment mechanisms of a country, in that it satisfies the main features of this overall definition The purpose of this book is to (a) extract the main lessons and experiences of the Western Hemisphere Payments and Securities Clearance and Settlement Initiative - Western Hemisphere Payments and Securities Settlement Forum (WHI-WHF) regarding the implementation of various reforms; (b) describe status of and major trends in payments and securities settlement systems worldwide and their implications for the LAC region; (c) summarize the detailed assessment findings for each LAC country in the following fields: (1) legal and regulatory framework, (2) main characteristics of the inter-bank exchange and settlement circuits, (3) retail settlement systems, (4) the role of the government as a major participant in the payments system, (5) foreign exchange and cross-border settlement, (6) the operation of the inter-bank money market, (7) aspects related to securities settlement such as the legal framework, clearance and settlement processes, settlement risks, operational reliability, custody, depositories' organizational arrangements, cross-border links, and (8) the oversight role of the central bank, coordination with the regulatory and supervisory role over securities settlement, and cooperation with the private sector; and (d) propose practical observations regarding the implementation of payments and securities settlement system reforms in the LAC region.